2018
DOI: 10.17507/jltr.0906.04
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Digital Game-based Learning: Video-games Principles and Applications in Foreign Language Learning

Abstract: During the present decade, researchers and educators of different fields have increased their attention towards digital game-based learning. The rise of interest towards this approach is partially connected to some important technological advances during the same period of time, such as the Smartphone, enhanced Internet connection from mobile devices, diversity and spread of free and low-cost video-games and educational applications in e-stores, development of speech recognition systems and artificial intellig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 69 publications
1
42
0
5
Order By: Relevance
“…The last cognitive function that is identified to be positively associated with VG is second language (L2) learning in that not only serious games but also commercial VGs provide players with the opportunity for language practice and acquisition [60]. Among various genres, MMORPGs, which are full with the opportunity of interaction between players, and between players and the VG environment in target language [61], are suggested as the efficient method for speaking practice [62] and are reported to facilitate the learning of L2 [63].…”
Section: Sgsmentioning
confidence: 99%
“…The last cognitive function that is identified to be positively associated with VG is second language (L2) learning in that not only serious games but also commercial VGs provide players with the opportunity for language practice and acquisition [60]. Among various genres, MMORPGs, which are full with the opportunity of interaction between players, and between players and the VG environment in target language [61], are suggested as the efficient method for speaking practice [62] and are reported to facilitate the learning of L2 [63].…”
Section: Sgsmentioning
confidence: 99%
“…Aside from solving problems and building projects, MMORPG players may also practice their language skills through their interaction with other speakers during sessions (Bytheway, 2015 ; Strachan, Kongmee, & Pickard, 2016 ; Canto & Jauregi, 2017 ; Chotipaktanasook & Reinders, 2018 ). This further concretizes the effectiveness of game-based learning, as language learners are able to participate in collaborative communication as well as acquire language through negotiation and language-learning strategies (Pitarch, 2018 ).…”
Section: Online Gamingmentioning
confidence: 86%
“…Research has also found a significance increase in students’ engagement, interaction and language production when they are playing online games such as OpenSim or Habbo Hotel during gameplay sessions (Berns, Rodriguez, & Gomez, 2013 ; Liao, Chang, & Chan, 2018 ; Pitarch, 2018 ). Students are able to interact and collaborate better with one another and are seen to be more critical when they perform specific activities in which they are able to use language precisely and solve language problems by paraphrasing, seeking clarification and responding to confirmation requests (Berns et al, 2013 ).…”
Section: Online Gamingmentioning
confidence: 99%
“…Our results corroborated previous research, which also demonstrated the positive effect of using mobile devices in language learning, albeit in other skills, such as writing and listening skills [ 44 , 45 ]. Speaking is a complex skill whose development not only requires ample input and but also requires repeated output [ 46 ], digital game-based mobile application can provide students with both visual and audio input via game elements and flexible delivery, which are likely to sustain learners’ efforts.…”
Section: Discussionmentioning
confidence: 99%